Knowledge on respectful maternity care among staff nurses: a descriptive survey - Devassy, Dhanya; X. , Sangeetha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Pregnancy is an especial, rousing and often blissful period in a woman’s life. Women may undergo various physiological changes during antepartum, intrapartum and postpartum period. The birthing room environment and health care provider’s attitude are important to minimize the pain and offer a positive childbirth experience. Across the world, women endure disrespect and abuse (D&A) during childbirth. Dearth of Respectful Maternity Care (RMC) from medical professionals like doctors and midwives may cause patients to feel unsatisfied with the healthcare system and lessen their obligation to seek antenatal (ANC), delivery, and postnatal care services. Objective of the study was to assess the existing knowledge on RMC among staff nurses working in the labour room. Methods: A non-experimental descriptive survey design was used to assess the knowledge on Respectful Maternity Care among staff nurses working in the labour room. Non-probability convenient technique was used to select 69 staff nurses from Ramaiah Medical College Hospital, Ramaiah Memorial Hospital, Motherhood Hospital, Lakshmi Maternity and Surgical Center and Aveksha Hospital, Bengaluru from April 2022 to May 2022. Structured knowledge questionnaire was used to assess the knowledge on respectful maternity care. Results: The overall knowledge score shows that 65.5% had moderately adequate knowledge on Respectful Maternity Care. The overall knowledge score mean was 16.72 with mean percentage of 64.30 and SD of ±3.438. Conclusions: Assessment and improvement in nurses’ knowledge will improve the quality of care as a means of enhancing safety during childbirth and positive childbirth experience.